2021
DOI: 10.5944/ried.24.2.29102
|View full text |Cite
|
Sign up to set email alerts
|

Validación de una plataforma de evaluación formativa de la competencia digital docente en tiempos de Covid-19

Abstract: La progresiva incorporación de las tecnologías digitales en la educación superior ha puesto de manifiesto la necesaria competencia digital docente (CDD). Una competencia que no solo implica conocimientos técnicos, sino también pedagógicos y de empoderamiento del estudiante. En la última década, algunas universidades han revisado sus planes de digitalización o transformación digital, alineando sus estrategias y políticas formativas en el desarrollo de esta competencia, algo que todavía se ha vuelto más necesari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 30 publications
(23 reference statements)
0
4
0
10
Order By: Relevance
“…The professors involved in this study, who could be labeled as Leaders or Pioneers [14], had a high DTC according to the classifications presented in the reviewed studies [14,23,25]. A high DTC not only implies skillful handling of technologies but also requires having a criterion to select the most appropriate teaching technologies in each situation, allowing teachers to enrich their teaching, develop the digital competence of their students, and continue developing professionally [24,28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The professors involved in this study, who could be labeled as Leaders or Pioneers [14], had a high DTC according to the classifications presented in the reviewed studies [14,23,25]. A high DTC not only implies skillful handling of technologies but also requires having a criterion to select the most appropriate teaching technologies in each situation, allowing teachers to enrich their teaching, develop the digital competence of their students, and continue developing professionally [24,28].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors [28,31,33,38,40,41,45,46] indicated that the pandemic has had a clear influence on university teaching. In relation to DTC, these authors also agreed that the pandemic has created the necessity of including digital tools to continue online classes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dos estudios cualitativos utilizan la entrevista (Suárez Guerrero et al, 2021) y en uno de ellos además realizaron grupos de discusión (Sales et al, 2020). Por otra parte, se han encontrado estudios que evalúan la CDD con una rúbrica (Marcano et al, 2020) o con una plataforma en la que el profesorado obtiene el resultado de la autoevaluación, y en función de este se le proponen actividades formativas (Viñoles-Cosentino et al, 2021). Existen estudios como el de Tomczyk et al (2021, en el que combinan herramientas que miden la CDD a través de la autopercepción con pruebas competenciales que permiten contrastar el nivel real adquirido.…”
Section: áMbito De Investigación 2 Descripción De Los Métodos De Inve...unclassified
“…Considering what was expressed by the professors, the socio-emotional bonding in relation to the formative assessment under the online and face-to-face modalities showed there to be a great difference. Where the online modality dominated the scenario, the formative evaluation was ineffective, monotonous, and boring, lacking in conversation that builds and energizes the teachinglearning process among the educational actors (Viñoles-Cosentino et al, 2021). This is the reason why the professor has ownership of what he says and does, inspiring and injecting emotion into the students to make them curious to learn.…”
Section: Socio-emotional Bondingmentioning
confidence: 99%